Picturing the invisible : exploring interdisciplinary synergies from the arts and the sciences - Coldwell, Paul; Morgan, Ruth M. (UCL Press, 2022)
"Picturing the Invisible presents different disciplinary approaches to articulating the invisible, that which is not known or that which is not provable. The challenge that we have seen is how to articulate these concepts, not only to those within a particular academic field but beyond, to other disciplines and society at large. As our understanding of the complexity of the world grows incrementally, so does our realisation that issues and problems can rarely be resolved within neat demarcations. Therefore, the importance of finding means of communicating across disciplines and fields becomes a priority. Whilst acknowledging the essential importance of the specialist academic, the capacity to understand other disciplines, their priorities, methodologies and even the language used can become crucial in being an effective instrument for change. This book brings together insights from leading academics from a wide range of disciplines including Art and Design, Curatorial Practice, Literature, Forensic Science, Medical Science, Psychoanalysis and Psychotherapy, Philosophy, Astrophysics and Architecture with a shared interest in exploring how, in each discipline, we strive to find expression for the invisible or unknown, and to draw out and articulate some of the explicit and tacit ways of communicating those concepts that transcend traditional disciplinary boundaries."--Page [4] of cover.